The LF02 automated luminescence reader - Baly, L.; Valle, R. A. D.; Chávez, A.; Gutiérrez, J. C.; Baly, M.; Cepero, T.; Lubián, H.; García, M.; Quesada, I.; Arteche, J.; et al. (Ancient TL, 2023)
In the present work the LF02 automated luminescence reader is introduced. The construction of the LF02 is part of a project aimed at creating capacities to support the activities of the luminescence dating laboratory at CEADEN in terms of carrying out sediment dating and basic research on quartz luminescence. To accomplish this task, a robust design with a basic structure capable of executing long measuring sequences was proposed. Along with the description of the reader, design concepts aimed at reducing the measurement time are analyzed in detail. To evaluate the effect of each design idea, the term reader productivity is defined. For the evaluation of the LF02 productivity, two different cases are analyzed. In the first one, the sample dose to recover is equivalent to 151 s of beta irradiation, while in the second case the time of irradiation is 833 s. The results show that the introduction of these ideas produces a significant reduction of time needed for completing a SAR sequence.